Nobody Knew How Complicated: Constraining The President's Power To (Re)Shape Health Reform. Issue 2 (May 2019) - Sanford, Sallie Thieme
Beginning on inauguration day, President Trump has attempted an executive repeal of the Affordable Care Act. In doing so, he has tested the limits of presidential power. He has challenged the force of institutional and non-institutional constraints. And, ironically, he has helped boost public support for the ACA's central features. The first two sections of this article respectively consider the use of the President's tools to advance and to subvert health reform. The final two sections consider the forces constraining the administration's attempted executive repeal. I argue that the most important institutional constraint, thus far, is found in multifaceted actions by states – and not only blue states. I also highlight the force of public voices. Personal stories, public opinion, and 2018 election results – bolstered by presidential messaging – reflect growing support for government-grounded options and statutory coverage protections. Indeed, in a polarized time, "refine and revise" seems poised to supplant "repeal and replace" as the conservative focus countering liberal pressure for a common option grounded in Medicare.